2000
DOI: 10.1128/aac.44.7.1961-1963.2000
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of Erm Methyltransferase Activity by Peptides Derived from Phage Display

Abstract: Combinatorial peptide display on phage M13 protein pIII was used to discover peptide sequences that selectively bind to ErmC methyltransferase from Bacillus subtilis. One peptide, Ac-LSGVIAT-NH 2 , inhibited methylation in vitro with a 50% inhibitory concentration of 20 M. Interestingly, the set of six peptides which inhibited ErmC stimulated ErmSF, a homologous methyltransferase from Streptomyces fradiae. Thus, Ac-LSGVIAT-NH 2 may not act directly at the catalytic center of ErmC, but may modulate its activity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2001
2001
2013
2013

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 9 publications
0
3
0
Order By: Relevance
“…These residues and motifs are generally well conserved among the Erm proteins and may represent potential targets for the development of inhibitors of this family of enzymes. Note that the application of combinatorial phage display technology has led to the discovery of several short peptides that bind to the ErmC protein and inhibit its activity (8). This type of approach provides an alternative method for the identification of Erm inhibitors.…”
Section: Discussionmentioning
confidence: 99%
“…These residues and motifs are generally well conserved among the Erm proteins and may represent potential targets for the development of inhibitors of this family of enzymes. Note that the application of combinatorial phage display technology has led to the discovery of several short peptides that bind to the ErmC protein and inhibit its activity (8). This type of approach provides an alternative method for the identification of Erm inhibitors.…”
Section: Discussionmentioning
confidence: 99%
“…However, Clancy et al 156 do not state explicitly that such experiments were done.) Though there is no indication of binding exosites for Erms, 158 Giannattasio and Weisblum 159 reported several peptide inhibitors of ErmC 0 (a soluble form of ErmC produced by B. subtilis), which they proposed acted at sites other than the active site of the enzyme.…”
Section: Ribosomal Methyltransferase Inhibitors: Embracing Epigenicity?mentioning
confidence: 99%
“…Although targeting efflux mechanisms might make sense for S. pneumoniae, the overall predominance of methyltransferase-mediated resistance to macrolides has led researchers to investigate the development of inhibitors for these enzymes. Erm inhibitors (Clancy et al 1995 ;Hajduk et al 1999), including inhibitor peptides identified by phage display (Giannattasio & Weisblum 2000), have been described, in one instance showing potentiation of azithromycin activity in MLS B -resistant Gram-positive and Gram-negative bacteria (Clancy et al 1995). Recently, S-adenosyl--homocysteine mimics have been reported as weak but promising inhibitors of Erm methyltransferases (Hanessian & Sgarbi 2000).…”
Section: Macrolidesmentioning
confidence: 99%